2018
DOI: 10.1136/thoraxjnl-2018-211731
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes from time of listing for lung transplantation in the UK: are there disease-specific differences?

Abstract: BackgroundThe demand for lung transplantation vastly exceeds the availability of donor organs. This translates into long waiting times and high waiting list mortality. We set out to examine factors influencing patient outcomes from the time of listing for lung transplantation in the UK, examining for differences by patient characteristics, lung disease category and transplant centre.MethodsData were obtained from the UK Transplant Registry held by NHS Blood and Transplant for adult lung-only registrations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…Individuals with shorter stature (under 162 cm) have an increased risk of death on the lung transplant waitlist [82,83]. This disadvantage is at least partially explained by the difficulties in finding donor lungs of the correct size and is of particular importance among pediatric lung transplant candidates.…”
Section: The Cf Foundation Recommends Lung Transplant Referral For Admentioning
confidence: 99%
“…Individuals with shorter stature (under 162 cm) have an increased risk of death on the lung transplant waitlist [82,83]. This disadvantage is at least partially explained by the difficulties in finding donor lungs of the correct size and is of particular importance among pediatric lung transplant candidates.…”
Section: The Cf Foundation Recommends Lung Transplant Referral For Admentioning
confidence: 99%
“…The challenges attributed to meeting supply with demand and having sufficient organ donation vary from country to country, thus limiting lung donor availability, and unfortunately, in some countries many IPF patients still die waiting on the lung transplant list [138][139][140]. Accordingly, the appropriate triage of IPF patients according to disease severity and setting-up priorities within the waiting list are of particular importance.…”
Section: Developments In Lung Transplantationmentioning
confidence: 99%
“…Such result is slightly better than Italian study by Borchi et al who assessed that 76.08% of CF patient were able to be transplanted among all patients with known endpoints from this study [29]. Kourliouros et al reported that according to the UK Transplant Registry, only 61% of CF patients will become graft recipients 3 years after registration in the United Kingdom’s Waitlist for Lung Transplantation [30]. In our facility, 21.95% of patients with CF died on the NLTWL with 50% of patients being on it for almost 1.5 years.…”
Section: Discussionmentioning
confidence: 63%